Çocuk katılımı farkındalık ölçeği (ÇKFÖ): Ölçek geliştirme, güvenirlik ve geçerlik çalışması - Polat, Berrak Deniz; Alkan Ersoy, Özlem; TORAN, MEHMET (My University, 2017)
Bu çalışmanın amacı, çocuk gelişimi ve okul öncesi öğretmenliği bölümünde okuyan öğrencilerin çocuk hakları bağlamında katılım hakkı ile ilgili görüşlerini belirlemeye yönelik bir ölçek geliştirmektir. İlk olarak literatür taranarak oluşturulan 98 maddelik ölçme aracı alanında uzman 7 kişiye gönderilmiştir. Yorum ve görüşleri doğrultusunda ölçeğe 43 madde değiştirilmeden olduğu gibi geçmiş, 2 madde eklenmiş, 10 madde öneriler doğrultusunda düzenlenmiş, maddeler yakınlık derecesine göre sıralanmış ve 55 maddelik 5’li likert tipi bir ölçek ön formu oluşturulmuştur. 55 maddeden oluşan taslak ölçek 2016-2017 eğitim öğretim yılı bahar döneminde İstanbul ilinde bulunan iki vakıf üniversitesindeki çocuk gelişimi ve okul öncesi öğretmenliği bölümlerinde okuyan toplam 481 gönüllü öğrenciye uygulanmıştır. Ölçek geliştirme sürecinde açımlayıcı faktör analizi, doğrulayıcı faktör analizi, güvenirlik analizleri, test-tekrar test gibi çeşitli analizler yapılmıştır. Bu analizler sonucunda 18 madde ve 5 alt ölçekten oluşan Çocuk Katılımı Farkındalık Ölçeği; çocuk gelişimi ve okul öncesi öğretmenliği öğrencilerinin çocuk hakları bağlamında katılım hakkı ile ilgili görüşlerini belirlemede geçerli ve güvenilir olduğunu kanıtlar niteliktedir.

The purpose of this study is to develop a scale for the purpose of determining the views of students in the Child Development and Preschool Teaching Department regarding the right to participate in the context of children's rights. Firstly, 98-article measurement tool which created by scanning the literature was sent to 7 experts. In the light of comments and opinions, 43 articles were passed on the scale, 2 articles added, 10 articles are arranged in line with the suggestions, the articles are ranked according to their degree of similarity and a 5-point 55 article likert-type scale pre-form was created. The draft scale consisting of 55 articles was applied to total of 481 volunteer students of departments of Child Development and Preschool Teaching at two foundation universities in Istanbul during 2016-2017 academic year spring term. In the scale development process, various analyses such as exploratory factor analysis, confirmatory factor analysis, reliability analysis, test-retest were conducted. As a result of these various analyses applied in the scale development process, the Child Participation Awareness Scale consisting of 18 articles and 5 subscales proves that; the scale is valid and reliable in determining the opinions departments of Child Development and Preschool Teacher students regarding the right to participate in the context of children's rights.
Child participation awareness scale (CPAS): Scale development, reliability and validity study
Keywords: Çocuk hakları; katılım hakkı; ölçek geliştirme; Children's rights; right for participation; scale development